Am I ready for ethical dilemma? The case of final Accounting students in UPM - Ngalim, Siti Manisah; Abd Talib, Maswati; Ho, Jia Ling (Universiti Putra Malaysia Press, 2015)
This study is done to explore the readiness of final year accounting students in UPM for cohort 2010/2014. It will evaluate the whole population of final year accounting students in order to identify their ethical level using the DIT-2 test, first developed by the late Professor James R. Rest of University of Minnesota who also formed the Centre for the Study of Ethical Development with Professor Muriel J. Bebeau in 1980